1979
DOI: 10.1128/aac.16.6.767
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Secretion Levels of Amikacin

Abstract: Amikacin was given to 14 noninfected men as three consecutive intramuscular injections (7.5 mg/kg) at 12-h intervals. Serum and bronchial secretion specimens were obtained at various times during flexible fiberoptic bronchoscopy after the final dose. Serum and bronchial secretion concentrations obtained between 1.5 and 2.0 h after the final dose ranged from 17 to 40 ug/ml and 2.3 to 8.4 ug/ml with a mean of 23.7 ± 2.9 and 5.23 ± 1.5 ug/ml, ±1 standard error of the mean, respectively. The highest bronchial secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
16
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…These results for the bid treatment group are consistent with previous observations with amikacin (6,8). The reported MICs of amikacin for Acinetobacter spp.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…These results for the bid treatment group are consistent with previous observations with amikacin (6,8). The reported MICs of amikacin for Acinetobacter spp.…”
supporting
confidence: 83%
“…The ratio of concentrations in serum to concentrations in bronchial secretions (BC max/SC max) remained relatively constant at about 30%, and it involved a nonsaturable transport system that was a purely passive mechanism. These results are consistent with previous results obtained with twice-daily regimens (6,8). In another study conducted with 12 tracheostomized patients, Even et al noted bronchial secretion-toserum ratios between 15 and 30%, which also occurred in the case of patients with impaired renal function (9).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Dose-scheduling studies were simultaneously performed; we tested human-like doses of 500, 2,000, and 4,000 mg, chosen based on the pilot concentration-effect study in test tubes, to be administered thrice daily in order to match some of the C max /MIC and percent time the concentration remains above the MIC (%T MIC ) in the once-a-day regimens. The dilution rates were set to achieve an amikacin half-life of 3 h, as encountered in serum and bronchial secretions (14,15). The amikacin concentrations achieved in all the HFS were validated by sampling each central compartment during the last 2 days at 0, 0.5, 2.7, 5.…”
mentioning
confidence: 99%
“…Antibiotic concentrations in blood are compared with the MIC for the infecting organism in an attempt to determine whether the antibiotic will be available in sufficient concentration to be effective. However, it has been demonstrated that even though adequate concentrations of aminoglycoside antibiotics are achievable in the blood, levels in bronchial secretions may be substantially lower (1,4). Such low antibiotic concentrations in bronchial secretions may contribute to the continuing high mortality rate for gram-negative-bacillary pneumonias.…”
mentioning
confidence: 99%